2015
DOI: 10.1007/s10826-015-0199-2
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Transmission of Perceived Bonding Styles and Paternal Emotion Socialization: Mediation Through Paternal Emotion Dysregulation

Abstract: We examined perceived parental styles, emotion socialization practices and emotion dysregulation among fathers from a community sample in order to understand the intergenerational transmission of normative parenting behaviors. The sample consisted of 217 fathers of school-age children ranging in age from 6 to 12 years. We used a cross-sectional design. The fathers completed a set of self-report questionnaires including parental boding instrument, difficulties in emotion regulation scale, and coping with childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…The higher the optimal score, the more likely the parents’ behaviors are to promote bonding with their children and indicate adaptive parenting. The Chinese PBI has demonstrated good reliability in previous studies with families from similar cultural backgrounds (e.g., Yan et al 2015). In this study, the internal consistency was .81 for the fathers and .91 for the mothers for optimal bonding, .81 for the fathers and .76 for the mothers for care, and .66 for the fathers and .71 for the mothers for overprotection.…”
Section: Methodsmentioning
confidence: 85%
“…The higher the optimal score, the more likely the parents’ behaviors are to promote bonding with their children and indicate adaptive parenting. The Chinese PBI has demonstrated good reliability in previous studies with families from similar cultural backgrounds (e.g., Yan et al 2015). In this study, the internal consistency was .81 for the fathers and .91 for the mothers for optimal bonding, .81 for the fathers and .76 for the mothers for care, and .66 for the fathers and .71 for the mothers for overprotection.…”
Section: Methodsmentioning
confidence: 85%
“…This interpretation is consistent with Barber’s (1996) speculation, that is, the impacts of psychological control are mainly dependent on the extent to which children perceive these behaviors as controlling behaviors. Furthermore, numerous studies have demonstrated the crucial impacts of the perception of the parenting and family atmospheres on emotion regulation, from early childhood to adulthood (e.g., Brenning, Soenens, Van Petegem, & Vansteenkiste, 2015; Houltberg, Henry, & Morris, 2012; Jaffe, Gullone, & Hughes, 2010; Luebbe et al, 2014; Yan, Han, & Li, 2016). However, observed parental psychological control measured actual controlling behaviors rather than to what extent children perceived them.…”
Section: Discussionmentioning
confidence: 99%
“…While peers are influential during adolescence (e.g., Sumter, Bokhorst, Steinberg & Westenberg, ), caregivers, and especially parents, remain the central adults in an adolescent's life, particularly for serious matters (Hombrados‐Mendieta, Gomez‐Jacinto, Dominguez‐Fuentes, Garcia‐Leiva & Castro‐Travé, ). As such, adolescent offspring may utilize coping strategies that mimic those of their mothers during times of stress because these are the strategies they have been socialized to enact (Yan, Han & Li, ). This is in line with existing research indicating that youth imitate the resilient coping behaviors of their parents and, in doing so, feel confident about their ability to handle challenging situations (Sprague et al., ).…”
Section: Discussionmentioning
confidence: 99%